The Influence Of The Role Of Situational Leadership In Increasing Teacher Commitment, Satisfaction And Motivation - Restalillah, Rida Restu; Hamdiah, Hamdiah; Tiara Gusnia, Tiara Gusnia; Pramodya Casqie Lunita, Pramodya Casqie Lunita; Amalia, Amalia; Anjeliana, Anjeliana; Pamela Grace, Pamela Grace (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2024)
This study aims to find out the impact of situational leadership on teacher satisfaction, commitment, and motivation in Jambi City. The results of the research that has been carried out show that situational leadership has a positive impact in improving job satisfaction and organizational commitment as well as teacher motivation. This study uses a quantitative method with SEM-PLS analysis. The results are consistent with previous studies, which show that a leadership style that adapts to individual situations and needs can contribute to teacher well-being and performance. However, no motivational influence on teacher satisfaction was found in the context of this study, unlike the findings of previous studies. The conclusion of this study is to emphasize the importance of adopting a situation-based leadership style in the context of education to create a working environment that motivates, satisfies, and consolidates the commitment of teachers. Implications of this research can contribute to the development of leadership strategies that focus on teacher well-being and the overall quality of education.